2018
DOI: 10.18553/jmcp.2018.24.4.335
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Costs per Month of Progression-Free Survival and Overall Survival: An Economic Model Comparing Everolimus with Cabozantinib, Nivolumab, and Axitinib for Second-Line Treatment of Metastatic Renal Cell Carcinoma

Abstract: Funding for this research was provided by Novartis, which was involved in all stages of study research and manuscript preparation. Ghate and Perez are employees of Novartis and own stock/stock options. Swallow, Messali, McDonald, and Duchesneau are employees of Analysis Group, which has received consultancy fees from Novartis. Study concept and design were contributed by Swallow, Messali, Ghate, and Perez, along with McDonald and Duchesneau. Swallow, Messali, McDonald, and Duchesneau collected the data, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…[28] As more new drugs were approved for second-line therapy of mRCC, BSC became less common in second-line settings and cost-effectiveness analyses were able to model clinical parameters from head-to-head trials, such as the AXIS (AXItinib vs. Sorafenib in advanced renal cell carcinoma) trial for axitinib vs. sorafenib [32] and the CheckMate 025 trial for nivolumab vs. everolimus. [33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38].…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
See 3 more Smart Citations
“…[28] As more new drugs were approved for second-line therapy of mRCC, BSC became less common in second-line settings and cost-effectiveness analyses were able to model clinical parameters from head-to-head trials, such as the AXIS (AXItinib vs. Sorafenib in advanced renal cell carcinoma) trial for axitinib vs. sorafenib [32] and the CheckMate 025 trial for nivolumab vs. everolimus. [33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38].…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
“…[33] Eight studies included both nivolumab and everolimus in the comparators [29][30][31][34][35][36][37][38] and these two drugs were directly compared in six. [29,31,[34][35][36]38]. Only two out of the six studies found nivolumab to be cost effective compared to everolimus.…”
Section: Cea: Mrcc 2nd Linementioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review which evaluated the cost-effectiveness of cabozantinib compared with other second-line therapies found that although cabozantinib was associated with favourable progression-free and overall survival, it was also one of the most expensive drugs (compared with everolimus, axitinib, nivolumab and sunitinib). In US dollars, costs of cabozantinib per patient per month of progression-free and overall survival were $17,864 and $11,166–$12,303, compared with $16,889 and $8,569–$9,724 with everolimus ( 32 ).…”
Section: Cost-effectivenessmentioning
confidence: 99%